2020
DOI: 10.3390/rs12193226
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Forest Cover and Fragmentation in Costa Rica with a Corrected Global Tree Cover Map

Abstract: Global tree cover products face challenges in accurately predicting tree cover across biophysical gradients, such as precipitation or agricultural cover. To generate a natural forest cover map for Costa Rica, biases in tree cover estimation in the most widely used tree cover product (the Global Forest Change product (GFC) were quantified and corrected, and the impact of map biases on estimates of forest cover and fragmentation was examined. First, a forest reference dataset was developed to examine how the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 91 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…For spectral characteristics, in addition to spectral bands of Landsat data (i.e., blue, green, red, near infrared, shortwave infrared 1, and shortwave infrared 2), the normalized difference vegetation index (NDVI) [45] and the enhancement vegetable index (EVI) [46] were used to distinguish vegetation from other land use types; the normalized difference build index (NDBI) [47] was applied to assist the monitoring of urban construction land and rural settlement; and the normalized difference water index (NDWI) [48] was used to detect water bodies. Simultaneously, topography greatly impacts the distribution of different land use types [49]. Therefore, we calculated the elevation and slope using DEM.…”
Section: Remote Sensing Image Features and Classifier Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…For spectral characteristics, in addition to spectral bands of Landsat data (i.e., blue, green, red, near infrared, shortwave infrared 1, and shortwave infrared 2), the normalized difference vegetation index (NDVI) [45] and the enhancement vegetable index (EVI) [46] were used to distinguish vegetation from other land use types; the normalized difference build index (NDBI) [47] was applied to assist the monitoring of urban construction land and rural settlement; and the normalized difference water index (NDWI) [48] was used to detect water bodies. Simultaneously, topography greatly impacts the distribution of different land use types [49]. Therefore, we calculated the elevation and slope using DEM.…”
Section: Remote Sensing Image Features and Classifier Parametersmentioning
confidence: 99%
“…where R is the number of threat factors; Y r is the set of grid cells on r's raster map; w r is the impact weight of threat factor r; A x is the accessible grid x; S jr indicates the relative sensitivity of landscape type j to threat factor r-the value is 0-1; i rxy is the impact distance of threat factor r, which can be divided into linear or exponential function of distance from threats to habitats [49].…”
Section: Food Supplymentioning
confidence: 99%
“…The system represents a state-of-the-art workflow and visualization scheme meant to be adopted as a forest data source by national institutions and park managers. However, given that the tree cover concept includes secondary vegetation, tree plantations, and some crops as forests, further adaptation through refinement and processing is needed for its local use [23][24][25]. Vargas et al [26] reported that Terra-I and GLAD alerts underestimate the number and extent of deforestation events occurring on the ground due to persistent cloud cover and a mismatch between MODIS spatial resolution and the small size of forest clearings (for Terra-I).…”
Section: Forest Cover Changementioning
confidence: 99%